Analysis of the Effect of Price, Facilities, Services, and Location on Consumer Satisfaction (Empirical Study of Glen Coffee & Glenmore Resto Consumers) - Ariyanto, Kiki Dwi; Supeni, Retno Endah; Hafidzi, Ahmad Hasan (inovator, 2023)
This study aims to analyze the effect of price, facilities, service, and location on consumer satisfaction at Glen Coffee & Resto Glenmore. The research method used is quantitative. This research uses Non-Probability Sampling. The sample in this study amounted to 80 respondents. The data collection instrument used a questionnaire. The dependent variable is the consumer satisfaction variable and the independent variable is price, facilities, service, and location, namely price, facilities, service, and location on consumer satisfaction Glen Coffee & Res- to Glenmore. The data analysis techniques used include descriptive statistical tests, data instrument tests (validity test, reliability test), classical assumption tests (normality test, multicollinearity, heteroscedasticity test), multiple linear regression analysis, and hypothesis testing (t-test, coefficient of determination). The data analysis used is multiple linear regression. All statements are valid, reliable, and normal. The results of multiple linear regression analysis using a t-test which state that the variables of price, facilities, services, and location have a significant effect on purchasing decisions.